IMPLEMENTATION OF E-GOVERNMENT IN THE NATIONAL INDUSTRIAL INFORMATION SYSTEM (SIINAS) IN DEPARTMENT OF TRADE AND INDUSTRY, JENEPONTO REGENCY - Anugerah Suci Nurpadilah; Andi Cudai Nur; Asri Nur Aina (Universitas Negeri Makassar, 2026)
This study aims to understand, analyze, and describe how the optimization of e-Government implementation in the reporting of the National Industrial Information System (SIINas) is carried out at the Department of Trade and Industry, Jeneponto Regency and its supporting and inhibiting factors. This research is qualitative in nature, employing data collection techniques such as observation, interviews, and documentation. The data obtained from the research are processed using an interactive model analysis, which includes data condensation, data display, and conclusion drawing. The results of the study indicate that the implementation of e-Government in the National Industrial Information System (SIINas) at the Jeneponto Regency Trade and Industry Office has not been running optimally. This is identified through the extent to which the elements of successful e-Government implementation have been implemented, consisting of support, capacity, and value. The support and capacity elements need to be improved again. Meanwhile, in the value element, SIINas has a good impact on the Jeneponto Trade and Industry Office and Small and Medium Industries (IKM). However, these benefits have not been felt evenly by IKM in Jeneponto. Supporting factors in the implementation of e-Government in the National Industrial Information System (SIINas) at the Jeneponto Regency Trade and Industry Office, namely coordination with other institutions related to the implementation of SIINas and direct assistance to the community. Meanwhile, inhibiting factors, namely the absence of a special budget allocation prepared for SIINas, minimal knowledge of SMEs about technology, lack of skilled human resources, and low awareness of business actors.